واقع تطبيق مجالات استراتيجية التمييز بالمؤسسة الاقتصادية الجزائرية- دراسة حالة: مؤسسة نقاوس مصبرات –باتنة- - حجازي, إسماعيل; زكري, أسماء (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2019)
تناولت هذه الدراسة تقييما لواقع تطبيق مجالات استراتيجية التمييز بالمؤسسة الاقتصادية الجزائرية "نقاوس مصبرات"، عن طريق المسح الميداني للظاهرة على مستوى وحدة إنتاج المشروبات الخاصة بالمؤسسة خلال الثلاثي الثالث من سنة 2016، وذلك اعتمادا على مقاربة كيفية لدراسة وتحليل الظاهرة عبر استخدام أسلوب المقابلات الفردية. وقد خلصت الدراسة في الأخير إلى قوة تطبيق مفهوم استراتيجية التمييز بشكل عام، مع وجود تفاوت نسبي في تطبيق مجالاتها كل على حده داخل المؤسسة. كلمات مفتاحية: استراتيجية التمييز، جودة المنتوج، التغليف، شبكة التوزيع، صورة العلامة. تصنيف ات JEL : L12؛ L66         Abstract : This study assessed the reality of application of the differentiation strategy areas in the organization economic Algerian "n'gaous conserves", through field survey of the phenomenon at the level of the soft drink production unit of the institution during the third quarter of 2016, we have been based on qualitative approach for the study and analysis of the phenomenon by using the individual interviews. The study concluded that in the latter there is a strong in the application of the concept of differentiation strategy in the organization in general, and with a relative disparity in the application of the areas of each separately within the institution. Keywords: differentiation strategy; product quality; packing; distribution network; brand image. Jel Classification Codes: L12 ; L66